High-strength refractory castable and preparation method thereof
By using bauxite aggregate, bauxite fine powder, alumina powder, silicon powder, aluminate cement, carbon fiber and modified acrylic polymer admixtures, the problem of insufficient strength of existing refractory castables under high temperature conditions is solved, and high temperature stability and mechanical strength are improved.
Patent Information
- Application Number
- CN202510091551.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-03-25
AI Technical Summary
Existing refractory castables are prone to brittle failure under high temperature conditions and have insufficient strength.
Bauxite aggregate, bauxite fine powder, alumina powder, silicon powder, aluminate cement, carbon fiber and modified acrylic polymer admixture are used as raw materials to prepare high-strength refractory castable by stirring and mixing.
The mechanical strength and stability of the castable material at high temperatures are improved, the flexural strength and compressive strength are enhanced, and the slump and density are maintained.
Smart Images

Figure CN119684017A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of refractory materials, and in particular to a high-strength refractory castable and a preparation method thereof. Background Art
[0002] Castables are generally made of aggregates, binders and water. After being cast and formed, they can be used in high-temperature kilns, incinerators and other fields. Therefore, high requirements are placed on the refractory properties of castables. However, refractory castables are mostly brittle materials, which are prone to brittle failure during high-temperature use. Therefore, it is necessary to improve the high-temperature strength of castables.
[0003] Chinese patent CN115159966B discloses a high-strength refractory castable and a preparation method thereof, wherein the raw materials for preparation include refractory aggregate, powder, binder and water reducer, wherein the water reducer is a polyvinyl alcohol modified polyurethane obtained by cross-linking reaction with polyvinyl alcohol after polycondensation of dimethylolbutyric acid, hydroxyl monomer of polyethylene glycol ether and isocyanate monomer to obtain polyurethane prepolymer, and the polyvinyl alcohol modified polyurethane is adsorbed on the surface of the castable particles, which can improve the mechanical properties of the castable under high temperature conditions. However, the reinforcing effect of polyvinyl alcohol modified polyurethane on the castable only depends on the polar groups on the polyvinyl alcohol modified polyurethane molecules, and the reinforcing effect is limited, and the strength of the castable needs to be improved. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a high-strength refractory castable and a preparation method thereof, so as to solve the problem in the prior art that the strength of the castable needs to be improved.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows: A method for preparing a high-strength refractory castable comprises the following steps: Step 1, weigh the raw materials; The raw materials include: refractory aggregate, binder, reinforcing agent and admixture; Wherein, the refractory aggregate includes bauxite aggregate, bauxite fine powder, alumina powder, and silicon powder; The reinforcing agent includes carbon fiber; The binder includes aluminate cement; The admixture is prepared by the following steps: S1. Add an emulsifier into deionized water, stir to dissolve, then add polyethylene glycol methacrylate and acrylic acid, stir and emulsify to obtain a pre-emulsion; A portion of the pre-emulsion is mixed with a portion of the initiator, and reacted. After the reaction is completed, the remaining pre-emulsion and the remaining initiator are added to continue the reaction. After the reaction is completed, rotary evaporation and purification are performed to obtain an acrylic acid polymer; S2, adding an acrylic acid polymer to tetrahydrofuran, stirring and dispersing, adding pyridine, succinic anhydride, and 4-dimethylaminopyridine, reacting, and after the reaction is completed, precipitating, filtering, washing, and drying to obtain a modified acrylic acid polymer; S3, adding the modified acrylic acid polymer to deionized water, stirring to dissolve, obtaining a modified acrylic acid polymer solution, adding an aqueous sodium hydroxide solution to the modified acrylic acid polymer solution, stirring, and obtaining an additive; Step 2: After mixing the admixture with water, add bauxite aggregate, bauxite fine powder, alumina powder, carbon fiber, silica powder and aluminate cement, stir and mix to obtain a high-strength refractory castable.
[0006] Preferably, in step one, the mass ratio of bauxite aggregate, bauxite fine powder, alumina powder, carbon fiber, silica powder, aluminate cement and admixture is (350-450):(250-350):(40-60):(20-30):(50-60):(200-300):(25-35).
[0007] Preferably, in the step 1: when preparing the admixture, in S1, the molar ratio of polyethylene glycol methacrylate to acrylic acid is 1:(1-2), the amount of deionized water is 8-12 times the mass sum of polyethylene glycol methacrylate and acrylic acid, the amount of emulsifier is 4-8% of the mass of deionized water, and the stirring and emulsification conditions are stirring and emulsifying at a speed of 800-1200 r / min for 20-40 min; The emulsifier includes sodium dodecylbenzene sulfonate; The initiator includes potassium persulfate.
[0008] Preferably, in the step 1: when preparing the admixture, in S1, the amount of the initiator is 3-5% of the sum of the mass of polyethylene glycol methacrylate and acrylic acid; A portion of the pre-emulsion accounts for 30-50% of the total mass of the pre-emulsion, and a portion of the initiator accounts for 20-40% of the total mass of the initiator; The remaining pre-emulsion accounts for 50-70% of the total mass of the pre-emulsion, and the remaining initiator accounts for 60-80% of the total mass of the initiator.
[0009] Preferably, in the step 1: when preparing the admixture, in S1, the reaction conditions are in an inert gas atmosphere at a temperature of 70-80° C. for 2-3 h, and the continued reaction conditions are in an inert gas atmosphere at a temperature of 70-80° C. for 6-8 h.
[0010] Preferably, in step 1: when preparing the admixture, in S2, the mass ratio of acrylic acid polymer, tetrahydrofuran, pyridine, succinic anhydride and 4-dimethylaminopyridine is 100:(600-800):(15-20):(20-30):(2-5).
[0011] Preferably, in the step 1: when preparing the admixture, in S2, the reaction conditions are reflux reaction at a temperature of 50-70° C. for 4-6 hours.
[0012] Preferably, in the step 1: when preparing the admixture, in S3, the mass ratio of the modified acrylic acid polymer to deionized water is 1:(8-12), the amount of sodium hydroxide aqueous solution added is such that the pH value of the modified acrylic acid polymer solution is 8-9, and the stirring conditions are at room temperature and at a speed of 200-400 r / min for 1-2 h.
[0013] Preferably, the sodium hydroxide aqueous solution includes 1 mol / L sodium hydroxide aqueous solution.
[0014] Preferably, in step 2: the amount of water added is 20-25% of the mass of bauxite aggregate, bauxite fine powder, alumina powder, carbon fiber, silica powder, aluminate cement, and admixtures, and the stirring condition is stirring and mixing at a stirring speed of 200-400r / min for 1-2h.
[0015] The invention discloses a high-strength refractory castable prepared by adopting the above-mentioned preparation method of the high-strength refractory castable.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The raw materials in the present invention include bauxite aggregate, bauxite fine powder, alumina powder, silica powder, aluminate cement, carbon fiber and admixtures. The raw materials are stirred and mixed with water to prepare a castable. The bauxite aggregate, bauxite fine powder, alumina powder and silica powder as refractory aggregates all have a high refractory temperature. The prepared castable has good high temperature stability and can maintain good mechanical strength at high temperatures. Aluminate cement as a refractory binder has the characteristics of high strength and high refractoriness. The castable prepared by using it in combination with aluminum-based refractory aggregate has a high refractory temperature. Carbon fiber is added to the castable as a high temperature reinforcing agent to effectively improve the toughness of the castable, thereby improving its flexural strength and compressive strength. The addition of admixtures can reduce the amount of water added, improve the dispersibility of refractory aggregates and binders, increase the fluidity and density of the castable, and thus improve the strength of the castable. In the present invention, when preparing the admixture, polyethylene glycol methacrylate and acrylic acid are polymerized to prepare an acrylic polymer with a comb-like structure polyether side chain. When the polymer is adsorbed on the surface of cement particles, the hydrophilic polyether side chain can stretch in water, so that a hydrophilic three-dimensional adsorption layer with a certain thickness is formed on the surface of the cement particles, and the steric hindrance between the cement particles is increased, thereby increasing the coagulation barrier between the cement particles, so that the castable maintains a good slump and increases the strength of the castable; the anionic polar group carboxyl is adsorbed on the surface of the cement particles, which can provide electrostatic repulsion, so that the cement particles are dispersed with each other, the flocculation structure is destroyed, the fluidity and density of the castable are increased, and the strength of the castable is high; in addition, the acrylic polymer reacts with succinic anhydride through the hydroxyl group at the end of the polyether side chain, so that more carboxyl groups are introduced, so that the electrostatic repulsion between the cement particles can be further increased, and the strength of the castable is further increased. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The present invention is a process flow chart for preparing a high-strength refractory castable; Figure 2 The schematic diagram of the reaction of preparing a modified acrylic acid polymer by reacting an acrylic acid polymer with succinic anhydride in the present invention; Figure 3 It is a line graph of the flexural strength measurement results obtained when the casting materials prepared in Examples 1-5 and Comparative Examples 1-2 are tested for performance in the present invention; Figure 4 It is a line graph of the compressive strength test results obtained when the castables prepared in Examples 1-5 and Comparative Examples 1-2 of the present invention are tested for performance. DETAILED DESCRIPTION
[0018] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0019] Example 1 This embodiment discloses a method for preparing a high-strength refractory castable, comprising the following steps: Step 1: Preparation of admixtures: S1. Add sodium dodecylbenzene sulfonate to deionized water, stir and dissolve at a speed of 250 r / min, then add polyethylene glycol methacrylate and acrylic acid, the molar ratio of polyethylene glycol methacrylate to acrylic acid is 1:1, the amount of deionized water is 8 times the mass of polyethylene glycol methacrylate and acrylic acid, the amount of sodium dodecylbenzene sulfonate is 4% of the mass of deionized water, and stir and emulsify at a speed of 800 r / min for 40 min to obtain a pre-emulsion; The pre-emulsion accounting for 30% of the total mass of the pre-emulsion and the potassium persulfate accounting for 20% of the total mass of the potassium persulfate are mixed, and the mixture is reacted at 70°C for 3 hours in a nitrogen atmosphere. After the reaction is completed, the pre-emulsion accounting for 70% of the total mass of the pre-emulsion and the potassium sulfate accounting for 80% of the total mass of the potassium persulfate are added, and the mixture is reacted at 70°C for 8 hours in a nitrogen atmosphere. After the reaction is completed, the deionized water solvent is removed by rotary evaporation at 70°C, ethanol 3 times the mass of the deionized water is added, and the mixture is stirred at a speed of 250 r / min for 60 minutes, filtered, and the filtrate is rotary evaporated at 50°C to remove the ethanol, to obtain an acrylic acid polymer; The dosage of potassium persulfate is 3% of the total mass of polyethylene glycol methacrylate and acrylic acid; S2, adding an acrylic acid polymer to tetrahydrofuran, stirring and dispersing at a speed of 250r / min for 30min, adding pyridine, succinic anhydride, and 4-dimethylaminopyridine, the mass ratio of acrylic acid polymer, tetrahydrofuran, pyridine, succinic anhydride, and 4-dimethylaminopyridine is 100:600:15:20:2, reflux reaction at 50°C for 6h, after the reaction is completed, adding methanol 3 times the mass of tetrahydrofuran for precipitation, filtering, washing the filtered precipitate with methanol 3 times, and drying it in a vacuum drying oven at 50°C for 24h to obtain a modified acrylic acid polymer; S3, adding a modified acrylic acid polymer to deionized water, wherein the mass ratio of the modified acrylic acid polymer to the deionized water is 1:8, stirring and dissolving at a speed of 250 r / min to obtain a modified acrylic acid polymer solution, adding a 1 mol / L sodium hydroxide aqueous solution to the modified acrylic acid polymer solution, wherein the amount of the 1 mol / L sodium hydroxide aqueous solution added is such that the pH value of the modified acrylic acid polymer solution is 8, stirring at room temperature at a speed of 200 r / min for 2 h to obtain an admixture; Step 2, weighing raw materials bauxite aggregate, bauxite fine powder, alumina powder, carbon fiber, silica powder, aluminate cement and admixture, the mass ratio of bauxite aggregate, bauxite fine powder, alumina powder, carbon fiber, silica powder, aluminate cement and admixture is 350:250:40:20:50:200:25; Step 3: After mixing the admixture with water, add bauxite aggregate, bauxite fine powder, alumina powder, carbon fiber, silica powder and aluminate cement. The amount of water added is 20% of the total mass of bauxite aggregate, bauxite fine powder, alumina powder, carbon fiber, silica powder, aluminate cement and admixtures. Stir and mix at a stirring speed of 200r / min for 2h to obtain a high-strength refractory castable.
[0020] Example 2 This embodiment discloses a method for preparing a high-strength refractory castable, comprising the following steps: Step 1: Preparation of admixtures: S1. Add sodium dodecylbenzene sulfonate to deionized water, stir and dissolve at a speed of 250 r / min, then add polyethylene glycol methacrylate and acrylic acid, the molar ratio of polyethylene glycol methacrylate to acrylic acid is 1:2, the amount of deionized water is 12 times the mass of polyethylene glycol methacrylate and acrylic acid, the amount of sodium dodecylbenzene sulfonate is 8% of the mass of deionized water, and stir and emulsify at a speed of 1200 r / min for 20 min to obtain a pre-emulsion; The pre-emulsion accounting for 50% of the total mass of the pre-emulsion and the potassium persulfate accounting for 40% of the total mass of the potassium persulfate are mixed, and the mixture is reacted at 80° C. for 2 hours in a nitrogen atmosphere. After the reaction is completed, the pre-emulsion accounting for 50% of the total mass of the pre-emulsion and the potassium sulfate accounting for 60% of the total mass of the potassium persulfate are added, and the mixture is reacted at 80° C. for 6 hours in a nitrogen atmosphere. After the reaction is completed, the deionized water solvent is removed by rotary evaporation at 70° C., ethanol 3 times the mass of the deionized water is added, and the mixture is stirred at a speed of 250 r / min for 60 minutes, filtered, and the filtrate is rotary evaporated at 50° C. to remove the ethanol, to obtain an acrylic acid polymer; The dosage of potassium persulfate is 5% of the total mass of polyethylene glycol methacrylate and acrylic acid; S2, adding an acrylic acid polymer to tetrahydrofuran, stirring and dispersing at a speed of 250r / min for 30min, adding pyridine, succinic anhydride, and 4-dimethylaminopyridine, the mass ratio of acrylic acid polymer, tetrahydrofuran, pyridine, succinic anhydride, and 4-dimethylaminopyridine is 100:800:20:30:5, reflux reaction at 70°C for 4h, after the reaction is completed, adding methanol 3 times the mass of tetrahydrofuran to precipitate, filtering, washing the filtered precipitate with methanol 3 times, placing it in a vacuum drying oven at 50°C and drying it for 24h to obtain a modified acrylic acid polymer; S3, adding a modified acrylic acid polymer to deionized water, wherein the mass ratio of the modified acrylic acid polymer to the deionized water is 1:12, and stirring and dissolving at a speed of 250 r / min to obtain a modified acrylic acid polymer solution, adding a 1 mol / L sodium hydroxide aqueous solution to the modified acrylic acid polymer solution, wherein the amount of the 1 mol / L sodium hydroxide aqueous solution added is such that the pH value of the modified acrylic acid polymer solution is 9, and stirring at room temperature at a speed of 400 r / min for 1 h to obtain an admixture; Step 2, weighing raw materials bauxite aggregate, bauxite fine powder, alumina powder, carbon fiber, silica powder, aluminate cement and admixture, the mass ratio of bauxite aggregate, bauxite fine powder, alumina powder, carbon fiber, silica powder, aluminate cement and admixture is 450:350:60:30:60:300:35; Step 3: After mixing the admixture with water, add bauxite aggregate, bauxite fine powder, alumina powder, carbon fiber, silica powder and aluminate cement. The amount of water added is 25% of the total mass of bauxite aggregate, bauxite fine powder, alumina powder, carbon fiber, silica powder, aluminate cement and admixtures. Stir and mix at a stirring speed of 400r / min for 1h to obtain a high-strength refractory castable.
[0021] Example 3 This embodiment discloses a method for preparing a high-strength refractory castable, comprising the following steps: Step 1: Preparation of admixtures: S1. Add sodium dodecylbenzene sulfonate to deionized water, stir and dissolve at a speed of 250 r / min, then add polyethylene glycol methacrylate and acrylic acid, the molar ratio of polyethylene glycol methacrylate to acrylic acid is 1:1.2, the amount of deionized water is 10 times the mass of polyethylene glycol methacrylate and acrylic acid, the amount of sodium dodecylbenzene sulfonate is 5% of the mass of deionized water, and stir and emulsify at a speed of 1000 r / min for 30 min to obtain a pre-emulsion; The pre-emulsion accounting for 35% of the total mass of the pre-emulsion and the potassium persulfate accounting for 25% of the total mass of the potassium persulfate are mixed, and the mixture is reacted at 75°C in a nitrogen atmosphere for 2.5 hours. After the reaction is completed, the pre-emulsion accounting for 65% of the total mass of the pre-emulsion and the potassium sulfate accounting for 75% of the total mass of the potassium persulfate are added, and the mixture is reacted for 7 hours in a nitrogen atmosphere at 75°C. After the reaction is completed, the deionized water solvent is removed by rotary evaporation at 70°C, ethanol 3 times the mass of the deionized water is added, and the mixture is stirred at a speed of 250 r / min for 60 minutes, filtered, and the filtrate is rotary evaporated at 50°C to remove the ethanol, to obtain an acrylic acid polymer; Among them, the dosage of potassium persulfate is 3.5% of the total mass of polyethylene glycol methacrylate and acrylic acid; S2, adding an acrylic acid polymer to tetrahydrofuran, stirring and dispersing at a speed of 250r / min for 30min, adding pyridine, succinic anhydride, and 4-dimethylaminopyridine, the mass ratio of acrylic acid polymer, tetrahydrofuran, pyridine, succinic anhydride, and 4-dimethylaminopyridine is 100:650:16:22:3, reflux reaction at 60°C for 5h, after the reaction is completed, adding methanol 3 times the mass of tetrahydrofuran for precipitation, filtering, washing the filtered precipitate with methanol 3 times, and drying it in a vacuum drying oven at 50°C for 24h to obtain a modified acrylic acid polymer; S3, adding the modified acrylic acid polymer to deionized water, the mass ratio of the modified acrylic acid polymer to the deionized water is 1:10, stirring and dissolving at a speed of 250r / min to obtain a modified acrylic acid polymer solution, adding 1mol / L sodium hydroxide aqueous solution to the modified acrylic acid polymer solution, the amount of 1mol / L sodium hydroxide aqueous solution added is such that the pH value of the modified acrylic acid polymer solution is 8.5, stirring at room temperature at a speed of 300r / min for 1.5h to obtain an admixture; Step 2, weighing raw materials bauxite aggregate, bauxite fine powder, alumina powder, carbon fiber, silica powder, aluminate cement and admixture, the mass ratio of bauxite aggregate, bauxite fine powder, alumina powder, carbon fiber, silica powder, aluminate cement and admixture is 380:270:45:22:53:225:27; Step 3: After mixing the admixture with water, add bauxite aggregate, bauxite fine powder, alumina powder, carbon fiber, silica powder and aluminate cement. The amount of water added is 21% of the mass of bauxite aggregate, bauxite fine powder, alumina powder, carbon fiber, silica powder, aluminate cement and admixtures. Stir and mix at a stirring speed of 300r / min for 1.5h to obtain a high-strength refractory castable.
[0022] Example 4 This embodiment discloses a method for preparing a high-strength refractory castable, comprising the following steps: Step 1: Preparation of admixtures: S1. Add sodium dodecylbenzene sulfonate to deionized water, stir and dissolve at a speed of 250 r / min, then add polyethylene glycol methacrylate and acrylic acid, the molar ratio of polyethylene glycol methacrylate to acrylic acid is 1:1.5, the amount of deionized water is 10 times the mass of polyethylene glycol methacrylate and acrylic acid, the amount of sodium dodecylbenzene sulfonate is 6% of the mass of deionized water, and stir and emulsify at a speed of 1000 r / min for 30 min to obtain a pre-emulsion; The pre-emulsion accounting for 40% of the total mass of the pre-emulsion and the potassium persulfate accounting for 30% of the total mass of the potassium persulfate are mixed, and the mixture is reacted at 75°C in a nitrogen atmosphere for 2.5 hours. After the reaction is completed, the pre-emulsion accounting for 60% of the total mass of the pre-emulsion and the potassium sulfate accounting for 70% of the total mass of the potassium persulfate are added, and the mixture is reacted at 75°C in a nitrogen atmosphere for 7 hours. After the reaction is completed, the deionized water solvent is removed by rotary evaporation at 70°C, ethanol 3 times the mass of the deionized water is added, and the mixture is stirred at a speed of 250 r / min for 60 minutes, filtered, and the filtrate is rotary evaporated at 50°C to remove the ethanol, to obtain an acrylic acid polymer; The dosage of potassium persulfate is 4% of the total mass of polyethylene glycol methacrylate and acrylic acid; S2, adding an acrylic acid polymer to tetrahydrofuran, stirring and dispersing at a speed of 250r / min for 30min, adding pyridine, succinic anhydride, and 4-dimethylaminopyridine, the mass ratio of acrylic acid polymer, tetrahydrofuran, pyridine, succinic anhydride, and 4-dimethylaminopyridine is 100:700:17.5:25:3.5, reflux reaction at 60°C for 5h, after the reaction is completed, adding methanol 3 times the mass of tetrahydrofuran for precipitation, filtering, washing the filtered precipitate with methanol 3 times, and drying it in a vacuum drying oven at 50°C for 24h to obtain a modified acrylic acid polymer; S3, adding the modified acrylic acid polymer to deionized water, the mass ratio of the modified acrylic acid polymer to the deionized water is 1:10, stirring and dissolving at a speed of 250r / min to obtain a modified acrylic acid polymer solution, adding 1mol / L sodium hydroxide aqueous solution to the modified acrylic acid polymer solution, the amount of 1mol / L sodium hydroxide aqueous solution added is such that the pH value of the modified acrylic acid polymer solution is 8.5, stirring at room temperature at a speed of 300r / min for 1.5h to obtain an admixture; Step 2, weighing raw materials bauxite aggregate, bauxite fine powder, alumina powder, carbon fiber, silica powder, aluminate cement and admixture, the mass ratio of bauxite aggregate, bauxite fine powder, alumina powder, carbon fiber, silica powder, aluminate cement and admixture is 400:300:50:25:55:250:30; Step 3: After mixing the admixture with water, add bauxite aggregate, bauxite fine powder, alumina powder, carbon fiber, silica powder and aluminate cement. The amount of water added is 22.5% of the total mass of bauxite aggregate, bauxite fine powder, alumina powder, carbon fiber, silica powder, aluminate cement and admixtures. Stir and mix at a stirring speed of 300r / min for 1.5h to obtain a high-strength refractory castable.
[0023] Example 5 This embodiment discloses a method for preparing a high-strength refractory castable, comprising the following steps: Step 1: Preparation of admixtures: S1. Add sodium dodecylbenzene sulfonate to deionized water, stir and dissolve at a speed of 250 r / min, then add polyethylene glycol methacrylate and acrylic acid, the molar ratio of polyethylene glycol methacrylate to acrylic acid is 1:1.8, the amount of deionized water is 10 times the mass of polyethylene glycol methacrylate and acrylic acid, the amount of sodium dodecylbenzene sulfonate is 7% of the mass of deionized water, and stir and emulsify at a speed of 1000 r / min for 30 min to obtain a pre-emulsion; The pre-emulsion accounting for 45% of the total mass of the pre-emulsion and the potassium persulfate accounting for 35% of the total mass of the potassium persulfate are mixed, and the mixture is reacted at 75°C in a nitrogen atmosphere for 2.5 hours. After the reaction is completed, the pre-emulsion accounting for 55% of the total mass of the pre-emulsion and the potassium sulfate accounting for 65% of the total mass of the potassium persulfate are added, and the mixture is reacted at 75°C in a nitrogen atmosphere for 7 hours. After the reaction is completed, the deionized water solvent is removed by rotary evaporation at 70°C, ethanol 3 times the mass of the deionized water is added, and the mixture is stirred at a speed of 250 r / min for 60 minutes, filtered, and the filtrate is rotary evaporated at 50°C to remove the ethanol, to obtain an acrylic acid polymer; The dosage of potassium persulfate is 4.5% of the total mass of polyethylene glycol methacrylate and acrylic acid; S2, adding an acrylic acid polymer to tetrahydrofuran, stirring and dispersing at a speed of 250r / min for 30min, adding pyridine, succinic anhydride, and 4-dimethylaminopyridine, the mass ratio of acrylic acid polymer, tetrahydrofuran, pyridine, succinic anhydride, and 4-dimethylaminopyridine is 100:750:19:28:4, and reflux reaction is carried out at 60°C for 5h. After the reaction is completed, adding methanol 3 times the mass of tetrahydrofuran for precipitation, filtering, washing the filtered precipitate with methanol 3 times, and drying it in a vacuum drying oven at 50°C for 24h to obtain a modified acrylic acid polymer; S3, adding the modified acrylic acid polymer to deionized water, the mass ratio of the modified acrylic acid polymer to the deionized water is 1:10, stirring and dissolving at a speed of 250r / min to obtain a modified acrylic acid polymer solution, adding 1mol / L sodium hydroxide aqueous solution to the modified acrylic acid polymer solution, the amount of 1mol / L sodium hydroxide aqueous solution added is such that the pH value of the modified acrylic acid polymer solution is 8.5, stirring at room temperature at a speed of 300r / min for 1.5h to obtain an admixture; Step 2, weighing raw materials bauxite aggregate, bauxite fine powder, alumina powder, carbon fiber, silica powder, aluminate cement and admixture, the mass ratio of bauxite aggregate, bauxite fine powder, alumina powder, carbon fiber, silica powder, aluminate cement and admixture is 430:320:55:28:57:280:33; Step 3: After mixing the admixture with water, add bauxite aggregate, bauxite fine powder, alumina powder, carbon fiber, silica powder and aluminate cement. The amount of water added is 24% of the mass of bauxite aggregate, bauxite fine powder, alumina powder, carbon fiber, silica powder, aluminate cement and admixtures. Stir and mix at a stirring speed of 300r / min for 1.5h to obtain a high-strength refractory castable.
[0024] Comparative Example 1 This comparative example discloses a method for preparing a high-strength refractory castable, comprising the following steps: Step 1: Preparation of admixtures: S1. Add sodium dodecylbenzene sulfonate to deionized water, stir and dissolve at a speed of 250 r / min, then add polyethylene glycol methacrylate and acrylic acid, the molar ratio of polyethylene glycol methacrylate to acrylic acid is 1:1, the amount of deionized water is 8 times the mass of polyethylene glycol methacrylate and acrylic acid, the amount of sodium dodecylbenzene sulfonate is 4% of the mass of deionized water, and stir and emulsify at a speed of 800 r / min for 40 min to obtain a pre-emulsion; The pre-emulsion accounting for 30% of the total mass of the pre-emulsion and the potassium persulfate accounting for 20% of the total mass of the potassium persulfate are mixed, and the mixture is reacted at 70°C for 3 hours in a nitrogen atmosphere. After the reaction is completed, the pre-emulsion accounting for 70% of the total mass of the pre-emulsion and the potassium sulfate accounting for 80% of the total mass of the potassium persulfate are added, and the mixture is reacted at 70°C for 8 hours in a nitrogen atmosphere. After the reaction is completed, the deionized water solvent is removed by rotary evaporation at 70°C, ethanol 3 times the mass of the deionized water is added, and the mixture is stirred at a speed of 250 r / min for 60 minutes, filtered, and the filtrate is rotary evaporated at 50°C to remove the ethanol, to obtain an acrylic acid polymer; The dosage of potassium persulfate is 3% of the total mass of polyethylene glycol methacrylate and acrylic acid; S2, adding an acrylic acid polymer to deionized water, the mass ratio of the acrylic acid polymer to the deionized water being 1:8, stirring and dissolving at a speed of 250 r / min to obtain an acrylic acid polymer solution, adding a 1 mol / L sodium hydroxide aqueous solution to the acrylic acid polymer solution, the amount of the 1 mol / L sodium hydroxide aqueous solution added being such that the pH value of the acrylic acid polymer solution is 8, stirring at room temperature at a speed of 200 r / min for 2 h to obtain an admixture; Step 2, weighing raw materials bauxite aggregate, bauxite fine powder, alumina powder, carbon fiber, silica powder, aluminate cement and admixture, the mass ratio of bauxite aggregate, bauxite fine powder, alumina powder, carbon fiber, silica powder, aluminate cement and admixture is 350:250:40:20:50:200:25; Step 3: After mixing the admixture with water, add bauxite aggregate, bauxite fine powder, alumina powder, carbon fiber, silica powder and aluminate cement. The amount of water added is 20% of the total mass of bauxite aggregate, bauxite fine powder, alumina powder, carbon fiber, silica powder, aluminate cement and admixtures. Stir and mix at a stirring speed of 200r / min for 2h to obtain a high-strength refractory castable.
[0025] Comparative Example 2 This comparative example discloses a method for preparing a high-strength refractory castable, comprising the following steps: Step 1: Preparation of admixtures: S1. Add sodium dodecylbenzene sulfonate to deionized water, stir and dissolve at a speed of 250 r / min, then add acrylic acid, the amount of deionized water is 8 times the mass of acrylic acid, the amount of sodium dodecylbenzene sulfonate is 4% of the mass of deionized water, stir and emulsify at a speed of 800 r / min for 40 minutes to obtain a pre-emulsion; The pre-emulsion accounting for 30% of the total mass of the pre-emulsion and the potassium persulfate accounting for 20% of the total mass of the potassium persulfate are mixed, and the mixture is reacted at 70°C for 3 hours in a nitrogen atmosphere. After the reaction is completed, the pre-emulsion accounting for 70% of the total mass of the pre-emulsion and the potassium sulfate accounting for 80% of the total mass of the potassium persulfate are added, and the mixture is reacted at 70°C for 8 hours in a nitrogen atmosphere. After the reaction is completed, the deionized water solvent is removed by rotary evaporation at 70°C, ethanol 3 times the mass of the deionized water is added, and the mixture is stirred at a speed of 250 r / min for 60 minutes, filtered, and the filtrate is rotary evaporated at 50°C to remove the ethanol, to obtain an acrylic acid polymer; Among them, the dosage of potassium persulfate is 3% of the mass of acrylic acid; S2, adding an acrylic acid polymer to deionized water, the mass ratio of the acrylic acid polymer to the deionized water being 1:8, stirring and dissolving at a speed of 250 r / min to obtain an acrylic acid polymer solution, adding a 1 mol / L sodium hydroxide aqueous solution to the acrylic acid polymer solution, the amount of the 1 mol / L sodium hydroxide aqueous solution added being such that the pH value of the acrylic acid polymer solution is 8, stirring at room temperature at a speed of 200 r / min for 2 h to obtain an admixture; Step 2, weighing raw materials bauxite aggregate, bauxite fine powder, alumina powder, carbon fiber, silica powder, aluminate cement and admixture, the mass ratio of bauxite aggregate, bauxite fine powder, alumina powder, carbon fiber, silica powder, aluminate cement and admixture is 350:250:40:20:50:200:25; Step 3: After mixing the admixture with water, add bauxite aggregate, bauxite fine powder, alumina powder, carbon fiber, silica powder and aluminate cement. The amount of water added is 20% of the total mass of bauxite aggregate, bauxite fine powder, alumina powder, carbon fiber, silica powder, aluminate cement and admixtures. Stir and mix at a stirring speed of 200r / min for 2h to obtain a high-strength refractory castable.
[0026] In the above embodiments and comparative examples, polyethylene glycol methacrylate was purchased from Shanghai Myrel Biochemical Technology Co., Ltd. with an average molecular weight of 400; bauxite aggregate was purchased from Yixing Guijing Refractory Electric Porcelain Factory with specifications of 3-5mm; bauxite fine powder was purchased from Yixing Guijing Refractory Electric Porcelain Factory with specifications of 80-120 mesh; alumina micropowder was purchased from Zibo Jinmi New Materials Co., Ltd. with a particle size of 325 mesh; carbon fiber was purchased from Nanjing Weida Composite Materials Co., Ltd. with item number: wd-4mm-w and specification: 4mm; silicon micropowder was purchased from Lingshou County Baixin New Materials Technology Co., Ltd. with a particle size of 1250 mesh; aluminate cement was purchased from Zhengzhou Kanghui Refractory Co., Ltd. with model number CA50-A600.
[0027] Test example The high-strength refractory castables prepared in Examples 1-5 and Comparative Examples 1-2 were tested for performance: the castables prepared in Examples 1-5 and Comparative Examples 1-2 were respectively poured into a mold of 150 mm × 25 mm × 25 mm, compacted, naturally cured at room temperature for 24 h, demolded, first dried at 110 ° C to constant weight, then heated to 1500 ° C at a heating rate of 5 ° C / min, and kept at 1500 ° C for 3 h to obtain a test sample; (1) Flexural strength: The flexural strength of the test sample was measured with reference to the standard GB / T3002-2017 "Test method for high temperature flexural strength of refractory materials". The test results are shown in Table 1:
[0028] (2) Compressive strength: The compressive strength of the test sample was measured with reference to the standard YB / T2208-1998 "Test method for high temperature compressive strength of refractory castables". The test results are shown in Table 2:
[0029] As shown in Table 1 and Table 2, the castable prepared by the present invention has good high temperature strength. The aggregate and binder in the present invention have high refractory temperature, the castable prepared has good high temperature stability, and can still maintain good strength at high temperature. Carbon fiber, as a high temperature resistant reinforcing agent, can effectively improve the toughness of the castable, thereby improving its flexural strength and compressive strength. The admixture is prepared from polyethylene glycol methacrylate and acrylic acid, and the molecule contains a polyether side chain with a comb-like structure, which can increase the steric hindrance between cement particles, so that the castable maintains a good slump and increases the strength of the castable; the anionic polar group carboxyl is adsorbed on the surface of the cement particles, and the electrostatic repulsion can make the cement particles dispersed from each other, increase the fluidity and density of the castable, and the strength of the castable is high; the acrylic polymer reacts with succinic anhydride through the hydroxyl group at the end of the polyether side chain, and introduces more carboxyl groups, which can further improve the electrostatic repulsion between cement particles, and the strength of the castable is further increased. Compared with Example 1, in Comparative Example 1, no carboxyl group is introduced into the hydroxyl group at the end of the polyether side chain of the acrylic polymer, the electrostatic repulsion is weakened, and the strength of the castable is reduced; in Comparative Example 2, no polyether side chain is introduced into the acrylic polymer, the steric hindrance between the cement particles is reduced, and the strength of the castable is also reduced.
[0030] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a high-strength refractory castable, characterized in that: The following steps are involved: Step 1, weigh the raw materials; The raw materials include: refractory aggregate, binder, reinforcing agent and admixture; Wherein, the refractory aggregate includes bauxite aggregate, bauxite fine powder, alumina powder, and silicon powder; The reinforcing agent includes carbon fiber; The binder includes aluminate cement; The admixture is prepared by the following steps: S1. Add an emulsifier into deionized water, stir to dissolve, then add polyethylene glycol methacrylate and acrylic acid, stir and emulsify to obtain a pre-emulsion; A portion of the pre-emulsion is mixed with a portion of the initiator, and reacted. After the reaction is completed, the remaining pre-emulsion and the remaining initiator are added to continue the reaction. After the reaction is completed, rotary evaporation and purification are performed to obtain an acrylic acid polymer; S2, adding an acrylic acid polymer to tetrahydrofuran, stirring and dispersing, adding pyridine, succinic anhydride, and 4-dimethylaminopyridine, reacting, and after the reaction is completed, precipitating, filtering, washing, and drying to obtain a modified acrylic acid polymer; S3, adding the modified acrylic acid polymer to deionized water, stirring to dissolve, obtaining a modified acrylic acid polymer solution, adding an aqueous sodium hydroxide solution to the modified acrylic acid polymer solution, stirring, and obtaining an additive; Step 2: After mixing the admixture with water, add bauxite aggregate, bauxite fine powder, alumina powder, carbon fiber, silica powder and aluminate cement, stir and mix to obtain a high-strength refractory castable.
2. The method for preparing a high-strength refractory castable according to claim 1, characterized in that: In the step 1, the mass ratio of bauxite aggregate, bauxite fine powder, alumina powder, carbon fiber, silica powder, aluminate cement and admixture is (350-450):(250-350):(40-60):(20-30):(50-60):(200-300):(25-35).
3. The method for preparing a high-strength refractory castable according to claim 1, characterized in that: In the step 1: when preparing the admixture, in S1, the molar ratio of polyethylene glycol methacrylate to acrylic acid is 1:(1-2), the amount of deionized water is 8-12 times the mass of the polyethylene glycol methacrylate and acrylic acid, the amount of emulsifier is 4-8% of the mass of deionized water, and the stirring and emulsification conditions are stirring and emulsifying at a speed of 800-1200 r / min for 20-40 min; The emulsifier includes sodium dodecylbenzene sulfonate; The initiator includes potassium persulfate.
4. The method for preparing a high-strength refractory castable according to claim 1, characterized in that: In the step 1: when preparing the admixture, in S1, the amount of the initiator is 3-5% of the total mass of polyethylene glycol methacrylate and acrylic acid; A portion of the pre-emulsion accounts for 30-50% of the total mass of the pre-emulsion, and a portion of the initiator accounts for 20-40% of the total mass of the initiator; The remaining pre-emulsion accounts for 50-70% of the total mass of the pre-emulsion, and the remaining initiator accounts for 60-80% of the total mass of the initiator.
5. The method for preparing a high-strength refractory castable according to claim 1, characterized in that: In the step 1: when preparing the admixture, in S1, the reaction conditions are to react in an inert gas atmosphere at a temperature of 70-80° C. for 2-3 hours, and the conditions for continuing the reaction are to react in an inert gas atmosphere at a temperature of 70-80° C. for 6-8 hours.
6. The method for preparing a high-strength refractory castable according to claim 1, characterized in that: In the step 1: when preparing the admixture, in S2, the mass ratio of acrylic acid polymer, tetrahydrofuran, pyridine, succinic anhydride, and 4-dimethylaminopyridine is 100:(600-800):(15-20):(20-30):(2-5).
7. The method for preparing a high-strength refractory castable according to claim 1, characterized in that: In the step 1: when preparing the admixture, in S2, the reaction conditions are reflux reaction at a temperature of 50-70° C. for 4-6 hours.
8. The method for preparing a high-strength refractory castable according to claim 1, characterized in that: In the step 1: when preparing the admixture, in S3, the mass ratio of the modified acrylic acid polymer to deionized water is 1:(8-12), the amount of sodium hydroxide aqueous solution added is such that the pH value of the modified acrylic acid polymer solution is 8-9, and the stirring condition is at room temperature and at a speed of 200-400 r / min for 1-2h.
9. The method for preparing a high-strength refractory castable according to claim 1, characterized in that: In the step 2, the amount of water added is 20-25% of the mass of bauxite aggregate, bauxite fine powder, alumina powder, carbon fiber, silica powder, aluminate cement and admixtures, and the stirring condition is stirring and mixing at a stirring speed of 200-400 r / min for 1-2 hours.
10. A high-strength refractory castable prepared by the method for preparing a high-strength refractory castable according to any one of claims 1 to 9.
Citation Information
Patent Citations
A high-strength refractory castable and its preparation method
CN115159966B
Cited By
Highly-doped lithium carbonate tailing paving stone and preparation method thereof
CN121426543A